Effects of Lisinopril on Bone Healing - Omar M.Alsaffar; Maha T. Al-Saffar; Abdulsattar S. Mahmood (The Indian Veterinary Journal, 2023)
This study set out to investigate whether treatment with lisinopril could aid in fracture healing, in addition, this study further aimed to closely understand the effects of lisinopril in terms of bone tissue healing time. Rabbits were obtained from the market and utilized as target samples for future experimental procedures after authorization. Lisinopril was used as the test drug in the trial. An ACE inhibitor drug called lisinopril is used to treat hypertension, heart failure and after a heart attack. Over several days, lisinopril was injected locally into the fracture site. The inflammation and re-epithelialization were measured and recorded for each study group on days 7, 14, and 21 after the fracture. Bone tissue samples were collected from the injured animals and fixed in formalin overnight. Tissue sections were then prepared, stained with eosin-hematoxylin and examined for pathological changes under the microscope. The effect of the drug was accompanied by low levels of granulation tissue and osteomalacia, as well as high levels of angiogenesis. Overall, bone regeneration was encouraged with the drug and there was no sign of bone loss in the experimental group, indicating that the drug is safe.